2016
DOI: 10.3343/alm.2016.36.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of NPM1 Type A Mutation Burden With Clinical Status and Outcomes in Acute Myeloid Leukemia Patients With Mutated NPM1 Type A

Abstract: BackgroundNucleophosmin gene (NPM1) mutation may be a good molecular marker for assessing the clinical status and predicting the outcomes in AML patients. We evaluated the applicability of NPM1 type A mutation (NPM1-mutA) quantitation for this purpose.MethodsTwenty-seven AML patients with normal karyotype but bearing the mutated NPM1 were enrolled in the study, and real-time quantitative PCR of NPM1-mutA was performed on 93 bone marrow (BM) samples (27 samples at diagnosis and 56 at follow-up). The NPM1-mutA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The prognostic implications of this specific immunophenotypic profile are not well known, although some studies show a greater overall survival in these patients [8]. We have no explanation for the discordant results between morphological blast count and NPM1 quantitation in BM performed after the second cycle of chemotherapy, given that these measurements seem to be very concordant [9].…”
Section: Discussionmentioning
confidence: 76%
“…The prognostic implications of this specific immunophenotypic profile are not well known, although some studies show a greater overall survival in these patients [8]. We have no explanation for the discordant results between morphological blast count and NPM1 quantitation in BM performed after the second cycle of chemotherapy, given that these measurements seem to be very concordant [9].…”
Section: Discussionmentioning
confidence: 76%
“…There were five main root nodes observed for mutations in FLT3, IDH2, NPM1, TP53, and upregulation of RAD21. Most of these mutations have been observed previously in AML [191] , [192] , [201] , [192] , [210] , [211] . Our first tree shows that mutations in FLT3 will precede mutations in WT1 [193] .…”
Section: Resultsmentioning
confidence: 83%
“…6 A good molecular marker for assessing the clinical status and predicting the outcomes in AML patients was Nucleophosmin 1 gene (NPM1) mutation. 14 Webersinke et al reported that as primary leukemogenic the mutations in exon 12 of the nucleophosmin (NPM1) gene have been described and event in up to 35% of adult acute myelogenous leukemia (AML) cases and they added that this type of AML is listed as provisional entity in the World Health Organization classification of tumors of the hematopoietic and lymphoid tissues. 15 Juliusson and Colleagues reported that mutations in Nucleophosmin 1 (NPM1) provide prognostic information with clinical relevance through choice of treatment and they found that significantly females more often had NPM1 mutation than male.…”
Section: Discussionmentioning
confidence: 99%
“… 6 A good molecular marker for assessing the clinical status and predicting the outcomes in AML patients was Nucleophosmin 1 gene (NPM1) mutation. 14 …”
Section: Discussionmentioning
confidence: 99%